Optimization of the Tahfiz Al-Qur'an Program through the Peer Teaching Method among Eighth-Grade Students at MTs Ma'arif NU 1 Kedungbanteng - Fattah Mutamassik Alhaq; Donny Khoirul Azis (The Future of Education Journal, 2026)
The Tahfidz Al-Qur'an program is one of the flagship programs developed in Islamic educational institutions to foster students' Qur'anic memorization skills while strengthening their religious character. However, the implementation of tahfidz programs often faces several challenges, including differences in students' memorization abilities, limited instructional time, and insufficient murajaah practices. One of the learning methods that can address these challenges is peer teaching. This study aims to describe the implementation of the peer teaching method in the Tahfidz Al-Qur'an program for eighth-grade students at MTs Ma'arif NU 1 Kedungbanteng. This research employed a qualitative approach using descriptive field research. Data were collected through observation, interviews, and documentation. Research participants consisted of tahfidz teachers and eighth-grade students involved in the Tahfidz Al-Qur'an program. Data analysis was conducted using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings revealed that the implementation of peer teaching was carried out through planning, implementation, and evaluation stages. Students with better memorization abilities were appointed as peer tutors to assist their classmates in memorization submission, murajaah activities, and recitation correction. The implementation of peer teaching positively contributed to improving memorization quality, learning motivation, cooperation, responsibility, and students' self-confidence. Supporting factors included teacher support, the availability of peer tutors, a religious school environment, and the boarding school background of several students. Meanwhile, inhibiting factors consisted of limited learning time, lack of murajaah at home, varying student abilities, and low confidence among some peer tutors.